Maintaining High-Quality Multidisciplinary Pain Medicine Fellowship Programs: Part II: Innovations in Clinical Care Workflow, Clinical Supervision, Job Satisfaction, and Postgraduation Mentorship for Pain Fellows During the COVID-19 Pandemic. Issue 8 (10th June 2020) - Kohan, Lynn; Sobey, Christopher; Wahezi, Sayed; Brancolini, Scott; Przkora, Rene; Shaparin, Naum; Spektor, Boris; Moeschler, Susan; Anitescu, Magdalena
Abstract: Background: Pain fellowship programs are facing unique challenges during the COVID-19 pandemic. Restrictions by state governments and the Centers for Disease Control and Prevention have resulted in a rapidly changing and evolving learning environment for today's fellows. Innovative solutions must be sought to maintain proper education and ensure the well-being of our trainees. Methods: We assembled a panel of pain program directors who serve as officers/board members of the Association of Pain Program Directors, offering guidance and recommendations to pain fellowship directors nationwide. Panel members evaluate the best available evidence and expert opinion on use of remote and virtual platforms in clinical care, adaptability to alterations in clinic and referral management, and provide guidance on postgraduate impact. Conclusions: The country is in the midst of an unprecedented pandemic. The impact on pain management fellowships has been significant and will likely last for months, resulting in extraordinary challenges to the administration of pain fellowship programs and the education of our fellows. Several strategies will help address these challenges, including employing telehealth capabilities to continue clinical experiences and providing trainees with opportunities to continue their professional growth beyond fellowship completion. Together, we can implement innovative solutions to overcome these challenges.